29+n=-(-5n-5)

Simple and best practice solution for 29+n=-(-5n-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 29+n=-(-5n-5) equation:


Simplifying
29 + n = -1(-5n + -5)

Reorder the terms:
29 + n = -1(-5 + -5n)
29 + n = (-5 * -1 + -5n * -1)
29 + n = (5 + 5n)

Solving
29 + n = 5 + 5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-5n' to each side of the equation.
29 + n + -5n = 5 + 5n + -5n

Combine like terms: n + -5n = -4n
29 + -4n = 5 + 5n + -5n

Combine like terms: 5n + -5n = 0
29 + -4n = 5 + 0
29 + -4n = 5

Add '-29' to each side of the equation.
29 + -29 + -4n = 5 + -29

Combine like terms: 29 + -29 = 0
0 + -4n = 5 + -29
-4n = 5 + -29

Combine like terms: 5 + -29 = -24
-4n = -24

Divide each side by '-4'.
n = 6

Simplifying
n = 6

See similar equations:

| 7(2+w)=6(w-9) | | 6=2+u | | 2(2x-6)m+2(x+3)m=26 | | 4n^2+9n+5= | | 5(2x-3)=x+3 | | 13x-8+2x-5=12x-2+2x | | -16=22 | | 7p+3+4p+5= | | 17=4(x+5)-5x | | 8y=y-56 | | .2d=-3 | | -5t+t+(-12t)= | | 328=2(8-w) | | 172=2x+4(6x+4) | | 4v^2-12v^2-5v+15=0 | | .20x+.92*10=.65(x+10) | | .75*.75-6= | | 7a^2+22a+3= | | -k=(k-10) | | 2x-6=6-2x | | 36x=81 | | x+21=-8 | | 16=v(v-6) | | 9x-20+6x-5=180 | | 41=-r+32 | | 2x^2-5x-12= | | 9x(4)=81 | | 9x(4)= | | 8T=-4 | | 7x+9=6x+20 | | 3.33x=30 | | 4.5-1.5y=5.4 |

Equations solver categories